Instrumenting the Earth: Next-Generation Sensor Networks and Environmental Science - Lehning, Michael; Dawes, Nicholas; Bavay, Mathias; Parlange, Marc; Nath, Suman; Zhao, Feng (The Fourth Paradigm: Data-Intensive Scientific Discovery, 2009)
Increasing environmental challenges worldwide and a growing awareness of global climate change indicate an urgent need for environmental scientists to conduct science in a new and better way. Existing large-scale environmental monitoring systems, with their coarse spatiotemporal resolution, are not only expensive, but they are incapable of revealing the complex interactions between atmospheric and land surface components with enough precision to generate accurate environmental system models.